An analytical model of the two basic situation strategies in table tennis - Zhang, H.; Zhou, Z. (International Journal of Performance Analysis in Sport, 2017)
To explore table tennis tactics frequently used by players with different racket hands, this study used 364 table tennis matches among elite players as samples and adopted an analytical model of two basic situation strategies to calculate the usage rates and scoring rates of different tactics. The results showed that (1) this model could be applied to the evaluation of concrete tactical behaviours of first four strokes for elite table tennis players; (2) in men`s matches, players typically serve a short ball or return with a touch short to control their opponents, and they then would attack first (such as with topspin) in the third or fourth strokes to increase their scoring rate; (3) in women`s matches, players usually return the ball with a push to take the initiative and attack each other (e.g. topspin against topspin, or topspin against attacking), indicating that female players have simpler tactics than male players and (4) there are certain differences in effective tactics that are usually adopted by male and female players, as well as by right-hand and left-hand players.